Darwin, Tennyson and Their Readers Explorations in Victorian Literature and Science - Purton, Valerie (Anthem Nineteenth-Century Series, 2013)
'Darwin, Tennyson and Their Readers: Explorations in Victorian Literature and Science' is an edited collection of essays from leading authorities in the field of Victorian literature and science, including Gillian Beer and George Levine. Darwin, Tennyson, Huxley, Ruskin, Richard Owen, Meredith, Wilde and other major writers are discussed, as established scholars in this area explore the interaction between Victorian literary and scientific figures which helped build the intellectual climate of twenty-first century debates.